Analysis of free SSL/TLS Certificates and their implementation as Security Mechanism in Application Servers. - Cueva Hurtado, Mario E.; Alvarado Sarango, Diego Javier (Enfoque UTE, 2017)
Security in the application layer (SSL), provides the confidentiality, integrity, and authenticity of the data, between two applications that communicate with each other. This article is the result of having implemented Free SSL / TLS Certificates in application servers, determining the relevant characteristics that must have a SSL/TLS certificate, the Certifying Authority generate it. A vulnerability analysis is developed in application servers and encrypted communications channel is established to protect against attacks such as man in the middle, phishing and maintaining the integrity of information that is transmitted between the client and server.